DECIZIA EFICIENTĂ. DE LA TEORIE LA PRACTICĂ - USM ADMIN (Moldova State University, 2007)
Day by day, pre-university managers have an activity. Knowing, the decision plays a very important role in this activity, we come with some suggestions about modalities of deciding - process. It contains three important stages (steps): I - pro - decision; II - the self - decision; III- the post - decision stage (step). Taking in consideration their using, the conditions, criteria of decision, the manager will find the answers to the questions and the efficiency of educational process will be better in using it. These aspects have their explanations in this article.